PERAN BANK SAMPAH MUTIARA BAGI MASYARAKAT DI KELURAHAN TUAH KARYA KOTA PEKANBARU - Umi Aulia Ramadhani; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research aims to find out the role of The Pearl Waste Bank and the benefits for the community in Tuah Karya Village, Pekanbaru City. As for the formulation of the problem in this study (1) What is the role of the Pearl Waste Bank in Tuah Karya Village of Pekanbaru City? (2) What are the benefits of Mutiara Waste Bank for the community in Tuah Karya Village of Pekanbaru City? Techniques in data collection in this study are observations, literature studies, questionnaires and documentation. This research was conducted at The Pearl Waste Bank located in Tuah Karya Village, Pekanbaru City with a sample of 78 people using simple random sampling techniques where bank customers who sampled this study. The data analysis technique in this study is quantitative descriptive using SPSS version 23. The results in this study explain what are the role of Bank Sampah Mutiara, namely the role of inviting the public in sorting waste with indicators of 5 statements classified as high, the role of waste banks to produce output (savings) with indicators 2 statements classified as high and the benefits of waste banks, namely benefits for environmental health with indicators 4 statements classified as very useful and benefits for social economic with indicators 3 statements are classified as very useful.  Keywords : Role, Benefits, Waste Bank